Iconicity and Sign Lexical Acquisition: A Review - Ortega, Gerardo (Frontiers in Psychology, 2017)
The study of iconicity, defined as the direct relationship between a linguistic form and its referent, has gained momentum in recent years across a wide range of disciplines. In the spoken modality, there is abundant evidence showing that iconicity is a key factor that facilitates language acquisition. However, when we look at sign languages, which excel in the prevalence of iconic structures, there is a more mixed picture, with some studies showing a positive effect and others showing a null or negative effect. In an attempt to reconcile the existing evidence the present review presents a critical overview of the literature on the acquisition of a sign language as first (L1) and second (L2) language and points at some factor that may be the source of disagreement. Regarding sign L1 acquisition, the contradicting findings may relate to iconicity being defined in a very broad sense when a more fine-grained operationalisation might reveal an effect in sign learning. Regarding sign L2 acquisition, evidence shows that there is a clear dissociation in the effect of iconicity in that it facilitates conceptual-semantic aspects of sign learning but hinders the acquisition of the exact phonological form of signs. It will be argued that when we consider the gradient nature of iconicity and that signs consist of a phonological form attached to a meaning we can discern how iconicity impacts sign learning in positive and negative ways.